2020
DOI: 10.1101/2020.08.23.20078964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mask Wearing and Control of SARS-CoV-2 Transmission in the United States

Abstract: Introduction: Cloth face coverings and surgical masks have become commonplace across the United States in response to the SARS-CoV-2 epidemic. While evidence suggests masks help curb the spread of respiratory pathogens, research is limited. Face masks have quickly become a topic of public debate as government mandates have started requiring their use. Here we investigate the association between self-reported mask wearing, social distancing and community SARS-CoV-2 transmission in the United States, as well as … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
45
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 27 publications
3
45
0
1
Order By: Relevance
“…In their paper on self-reported face mask wearing and control of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission in the US, Rader and colleagues 1 showed an elegant ecological analysis of data from across the US, estimating the effect of face mask use on the transmission of COVID-19 infection. The authors made use of online survey responses of mask usage from thousands of individuals across the country over time to measure the relationship between mask wearing and community transmission control, as characterised by the instantaneous reproductive number.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In their paper on self-reported face mask wearing and control of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission in the US, Rader and colleagues 1 showed an elegant ecological analysis of data from across the US, estimating the effect of face mask use on the transmission of COVID-19 infection. The authors made use of online survey responses of mask usage from thousands of individuals across the country over time to measure the relationship between mask wearing and community transmission control, as characterised by the instantaneous reproductive number.…”
mentioning
confidence: 99%
“…The study of Rader and colleagues suggests that, in the US, risk-compensation does not cancel out the positive effect of face masks, but whether the US is representative of other countries is arguable. 1 On a policy level, the possibility of risk compensation, uncertainty about the magnitude of the reduction in transmission due to masks, and the result that the effect of face masks can be even greater when combined with other control measures, means maintaining other measures, such as physical distancing, contact tracing, testing, isolation, and quarantine, is still necessary.…”
mentioning
confidence: 99%
“…Mask wearing has been shown to be effective at preventing the transmission of SARS-CoV-2 and remains a key public health intervention for mitigating the COVID-19 pandemic (1,2). Mask wearing requires high population-level compliance (4) and is most effective at preventing onward transmission if both infected and susceptible individuals are wearing a mask at the time of contact (3). Inconsistent mask wearing policies and limited enforcement mechanisms have resulted in differential rates of mask uptake across the United States (2)(3)(4).…”
mentioning
confidence: 99%
“…Mask wearing requires high population-level compliance (4) and is most effective at preventing onward transmission if both infected and susceptible individuals are wearing a mask at the time of contact (3). Inconsistent mask wearing policies and limited enforcement mechanisms have resulted in differential rates of mask uptake across the United States (2)(3)(4). Some ecological and individual studies have found associations with reported mask wearing and changes in the SARS-CoV-2 transmission rate or self-reported positivity (1,4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation